From Reading Comprehension to Verbal Creativity - Violeta Teodora LUNGEANU (ACROSS)
A segment of literature in continuous expansion, texts of the biographical genre, represent a fertile ground for the development of communication competence due to their proximity to the referential, particularly in terms of understanding the written text. Drawing equally from fantasy and reality, journals, memoirs, autobiographies, and even autofictions bring to the forefront the way language operates, from the microstructural level of the word to the macrostructure of discourse and even meta-discourse, to name a certain reality. From this perspective, the current study aims to present a series of strategies that valorize this category of texts from the standpoint of communication competence, proposing several models of reception based on the staged realization of comprehension processes and an understanding of the poetic nature of language and how it can manifest its expressive resources in communication.